MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN MELALUI GAMBAR BERSERI BAGI ANAK TUNAGRAHITA RINGAN KELAS D III YAPEM TARUSAN PESISIR SELATAN - Suhaimi - Suhaimi (Jurnal Penelitian Pendidikan Khusus, 2013)
This research is originated from the results of the research carried out in asessmen SLB Yapem Tarusan South Coast to mild mental retardation students grade D III who had the initials T, R, and A. Where the child is able to read but he could not understand what was in the reading passage. This study aims to meninngkatkan child's ability in reading comprehension using images beamed premises. This study uses classroom action research (classroom action reseach) that dikukan to collaborate with colleagues. This subject is the researchers themselves who act as a classroom teacher and three students of class D III Tunagrahita Yapem Tarusan light in SLB school year 2012/2013. The implementation of this study in two cycles. Data was collected using a test given to students and documentation. The tests analyzed quantitatively. The results of this study indicate that 1) improve the learning process of reading comprehension was conducted in two cycles. Every cycle there is planning, implementing research activities include initial, core, end, observation and reflection. 2) The teaching reading comprehension in the first cycle of reading ability pemahama child has reached 75%. In the second cycle of reading comprehension ability of children has reached 95%. From the results we can conclude the presentation of the data there is an increasing students' reading comprehension skills by using pictures beamed then suggested to the teachers to use the images glow in teaching reading comprehension next